Transdermal delivery of traditional Chinese medicine patch vs. NSAIDs patch for alleviating inflammation and relieving pain for early-stage knee osteoarthritis: a retrospective case control study - Wang, Shoufeng; Guan, Jingtao; Gong, Wanran; Bao, Bingbo (Frontiers in Pharmacology, 2025)
BackgroundThe effects of transdermal delivery of traditional Chinese medicine (TCM) patch for early-stage knee osteoarthritis (EKOA) is unclear.ObjectiveThis study is aimed to compare the therapeutic effects of a type of TCM topical drug-Xiaotong patch with NSAIDs topical drug-flurbiprofen patch to treat EKOA.MethodsThis retrospective case control study included 42 EKOA patients from October 2023 to September 2024. Patients were divided into Xiaotong patch group and flurbiprofen patch group. The baseline characteristics, such as demographic and epidemiological information were collected. The main outcome measured was the alteration in Visual Analogue Scale (VAS) score following treatment. The secondary outcomes included inflammatory markers, like cytokine tumor necrosis factor-alpha (TNF-α) and erythrocyte sedimentation rate (ESR).ResultsThe 42 EKOA patients were divided into two groups averagely. They received the transdermal patch therapy daily for 14 days. The primary outcome-pain assessment based on VAS score showed a prominent decrease in both groups compared with the values before treatment (P < 0.05). There were no significant differences between groups after treatment (P > 0.05). For the secondary outcomes, TNF-α and ESR were included for evaluating the pre- and post-treatment findings. The results also indicated the inflammatory conditions were alleviated by transdermal delivery of drugs from TCM patch or NSAIDs patch. Similarly, the data showed a comparable anti-inflammatory effect between groups (P > 0.05).ConclusionThe TCM transdermal patch exerts a similar effect on the EKOA in the aspects of pain relief and regulating inflammation for a short-term treatment as NSAIDs patch. It may provide an alternative for clinical management of EKOA.